Design and development of a porous heterogeneous combustor for efficient heat production by combustion of liquid and gaseous fuels. (1st October 2016) - Terracciano, Anthony Carmine; Vasu, Subith S.; Orlovskaya, Nina
Highlights: Design scheme for a bi-fuel heterogeneous combustor featuring silicon carbide ceramic media within the combustion chamber. Combustor operation of both lean and ultra rich fuel-air mixtures. Suggested applications for heterogeneous combustors. Abstract: This work focuses on the design and operation of a heterogeneous combustor capable of operating on both gaseous and liquid fuels, featuring a highly porous (up to 90% porosity) silicon carbide ceramic media within the combustion chamber where the combustion reactions take place. Four interlinked devices – a heat exchanger, a vaporization chamber where liquid fuel may be injected, a mixing chamber, and combustion chamber – comprise the flow loop of the combustor. Operation of the combustor is presented using temperatures recorded via thermocouples at various locations in the flow loop as well as along the axis of the combustion chamber. Demonstration of the combustor's ability to operate on gaseous methane and air at a low equivalence ratio of 0.50 is presented across various total flow rates. Additionally, the ability of the combustor to operate on liquid fuel was also verified upon the inclusion of kerosene in the fuel-air mixture.